Virgin Queen and Aging Monarch: Contesting Images of Queen Elizabeth in the Last Decade of Her Reign - Stróbl, Erzsébet (FOCUS: Papers in English Literary and Cultural Studies, 2024)
The following paper will analyze the image of Queen Elizabeth in the last decade of her reign, examining both excessive praise and dissenting undercurrents detectable in the works of such older writers as John Lyly and younger talents like William Shakespeare. The three parts of the paper, which look at examples of official praise, Catholic slander, and artistic equivocation, will attempt to draw attention to the conflicting images of Queen Elizabeth as the awe-inspiring Virgin Queen and the lonely aging monarch at the twilight of the Tudor period.